2019
DOI: 10.3390/agronomy9060294
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control Ability of Single Sown Cover Crops Compared to Species Mixtures

Abstract: To achieve efficient weed control through cover cropping, the plant species chosen needs particular consideration. Combing different cover crop (CC) species in mixtures may increase the number of provided ecosystem services, including reliable suppression of weeds. We tested the weed suppression ability of single CC species and CC mixtures in a field trial during the autumn-to-winter growing season of 2016 and 2017. Anethum graveolens L. (dill), Raphanus sativus var. oleiformis Pers. (oilseed radish), Avena st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…These results are congruent with recent research showing cover crop mixtures are rarely if ever more productive or weed suppressive than the best-performing monoculture (Baraibar et al 2018;Blesh et al 2019;Creamer et al 1996;Finney et al 2016;Florence et al 2019;MacLaren et al 2019;Nelson et al 2011;Osipitan et al 2018;Schappert et al 2019;Smith et al 2014;Wortman et al 2012). The majority of these studies examined mixture performance for a single temporal cover-cropping niche.…”
Section: Spatiotemporal Variability In Weed Suppressionsupporting
confidence: 87%
“…These results are congruent with recent research showing cover crop mixtures are rarely if ever more productive or weed suppressive than the best-performing monoculture (Baraibar et al 2018;Blesh et al 2019;Creamer et al 1996;Finney et al 2016;Florence et al 2019;MacLaren et al 2019;Nelson et al 2011;Osipitan et al 2018;Schappert et al 2019;Smith et al 2014;Wortman et al 2012). The majority of these studies examined mixture performance for a single temporal cover-cropping niche.…”
Section: Spatiotemporal Variability In Weed Suppressionsupporting
confidence: 87%
“…Mixture species with different characteristics create a single crop to perform various functions [132]. However, weed management studies have shown that mixture performs better when composed of highly competitive species since biomass is a major predictor of weed suppression [133][134][135][136]. Furthermore, Florence and McGuire [137] performed a meta-analysis on 27 studies and found that mixture and monoculture cover crops perform comparably equal in seven metrics (biomass, N, weed, water, biology, yield, and stability).…”
Section: Cover Cropsmentioning
confidence: 99%
“…High biomass production can increase the effect of competition (den Hollander et al, 2007;Tobin et al, 2012) and many studies have highlighted the relation between cover crop biomass and weed control (e.g. Bhaskar et al, 2018;Florence et al, 2019;Osipitan et al, 2019;Schappert et al, 2019). Nevertheless, cover crop biomass is not always a good predictor of weed control (Baraibar et al, 2018;Kunz et al, 2016) and some authors like Dorn et al (2015) suggest that rapid plant development after sowing is more important than the final biomass.…”
Section: Cover Crop Performance and Weed Controlmentioning
confidence: 99%
“…Some authors suggest that increased cover crop diversity results in greater weed suppression (Akemo et al 2000;Brennan and Smith 2005;Lawson et al 2015), while others are more nuanced (Baraibar et al, 2018;Finney et al, 2016;Florence and McGuire, 2020;Schappert et al, 2019;Smith et al, 2014). In our study, average weed control efficiency by pure and mixed cover crop species was similar.…”
Section: Cover Crop Performance and Weed Controlmentioning
confidence: 99%